The Creative Legacy of the Great Russian Poet Boris Pasternak: Traditions and Innovation in His Poetic Works - Supian Supian; Ekaterina Prikhoda; Ruswan Dallyono; Ladinata Ladinata; Tri Yulianty Karyaningsih; Miksalmina Miksalmina (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This study examines the poems of Boris Pasternak, the famed Russian literary figure. It analyzes and compares the poet's works with those of his contemporaries and predecessors’. Some motifs, themes, images, and characteristic features of the stylistics and tropics of poetic creativity in Pasternak's lyrics were revealed, which signify the influence of traditions and innovation. By employing several literary criticism methods, namely those of close reading, a structuralist analysis, and biographical criticism, this study found that there is a wealth of themes both old and new in Pasternak’s poetry. These themes were mostly derived from past authors, which confirm the findings of Baróthy (2015), Han (2015), and Polivanova & Polivanov (2018). These themes were then reconstructed in Pasternak’s works in a way that signify these works as a celebration of the old and the welcoming of the new in the Russian literary tradition. This study has cemented Boris Pasternak’s role as a hub linking the old and the new generations in Russian literature.